A RECENT UPDATE ON HISTOGENESIS OF ADENOMATOID ODONTOGENIC TUMOR: A REVIEW - AHMED, SAHANAZ P; ARULMOZHI, NANDAKUMAR; RAMYA, RAMADAS; KARUNYA, KRISHNAKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Adenomatoid odontogenic tumor (AOT) is a relatively rare benign, epithelial tumor of odontogenic origin. There is varying class of thoughts contemplating this lesion to be a hamartoma or neoplastic growth of odontogenic epithelium. Controversy regarding the histogenesis of the lesion is plentiful in earlier literature. The recent advent of immunohistochemical and ultrastructural studies has aided in throwing light on the tissue of origin of this tumor. This review aims at understanding the evolving concepts of histogenesis of AOT to better understand the biological behavior of the lesion. The review of AOT was carried out using PubMed and Google Scholar databases and 39 articles from the year 2001 to 2016 which contributed to the histogenesis of AOT were included for review. Since the origin of the cystic lining is similar to a reduced enamel epithelium and not the dental lamina, we propose the former to be the progenitor of AOT. Furthermore, we consider extra-follicular, as well as peripheral AOTs, originate from the remnants of Hertwig’s epithelial root sheath (epithelial rests of Malassez), which complies with the common histology for all these variants.